2017
DOI: 10.1021/acs.energyfuels.7b02011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gaseous Chemistry in H2–O2–N2 Combustion over Platinum at Fuel-Lean Stoichiometries and Pressures of 1.0–3.5 bar

Abstract: The catalytic and gas-phase combustion of fuel-lean H2–O2–N2 premixtures was investigated in a channel coated with platinum at pressures 1.0–3.5 bar, a range encompassing microreactors in portable power generation systems and passive hydrogen recombiners in nuclear power plants. One-dimensional Raman spectroscopy assessed the progress of catalytic hydrogen combustion, while planar laser-induced fluorescence (LIF) of the hydroxyl radical monitored gaseous combustion. Simulations were performed using a 2-D code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Despite the common opinion that hydrogen autoignition initiates at 585 °C (literature reflecting value for gaseous ignition of hydrogen/air mixtures at 1 bar), different temperatures have been experimentally discovered for hydrogen autoignition over Pt-based catalyst. It was stated that there are four routes between the heterogeneous (catalytic combustion) and homogeneous (gas-phase combustion) reaction pathways: (i) promotion of homogeneous ignition due to the exothermicity of the catalytic pathway that heats up the reactor walls and consequently the flowing gas; (ii) catalytic combustion promoted by the near-wall depletion of the deficient reactant (hydrogen fuel); (iii) promotion of one of the pathways via the major species produced by the catalytic pathway over the gaseous induction zone (for example, water generated during CHC chemically inhibits homogeneous ignition in hydrogen/air mixtures while it promotes homogeneous ignition in methane/air mixtures); and (iv) catalytic adsorption/desorption reactions of radical species . For example, it has been demonstrated that homogeneous ignition of hydrogen/air mixtures requires the temperature of the reactor wall to be at least 927 °C at atmospheric pressure. , In a study by Sui et al, the autoignition of hydrogen was possible only at the reactor wall temperature of 827 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the common opinion that hydrogen autoignition initiates at 585 °C (literature reflecting value for gaseous ignition of hydrogen/air mixtures at 1 bar), different temperatures have been experimentally discovered for hydrogen autoignition over Pt-based catalyst. It was stated that there are four routes between the heterogeneous (catalytic combustion) and homogeneous (gas-phase combustion) reaction pathways: (i) promotion of homogeneous ignition due to the exothermicity of the catalytic pathway that heats up the reactor walls and consequently the flowing gas; (ii) catalytic combustion promoted by the near-wall depletion of the deficient reactant (hydrogen fuel); (iii) promotion of one of the pathways via the major species produced by the catalytic pathway over the gaseous induction zone (for example, water generated during CHC chemically inhibits homogeneous ignition in hydrogen/air mixtures while it promotes homogeneous ignition in methane/air mixtures); and (iv) catalytic adsorption/desorption reactions of radical species . For example, it has been demonstrated that homogeneous ignition of hydrogen/air mixtures requires the temperature of the reactor wall to be at least 927 °C at atmospheric pressure. , In a study by Sui et al, the autoignition of hydrogen was possible only at the reactor wall temperature of 827 °C.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that homogeneous ignition of hydrogen/air mixtures requires the temperature of the reactor wall to be at least 927 °C at atmospheric pressure. , In a study by Sui et al, the autoignition of hydrogen was possible only at the reactor wall temperature of 827 °C. Also, the authors stated that safe recombiner operation is in the pressure range of 2.0–2.5 bar …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further noted that straight channels are not a convenient idealization, but are used in both laboratory and industrial catalytic systems (see Refs. [23,[32][33][34]37,38]).…”
Section: Development Of Catalytic Boundary Conditionmentioning
confidence: 99%
“…There are considerably fewer literature investigations on heterogeneous reactions by LBM, even though this topic is of main interest in many practical systems such as automotive exhaust gas treatment, fuel processing, synthesis of chemicals, power generation, geochemical applications [21,22], hydrogen recombiners in nuclear power plants [23], etc. Kang et al [14] advanced the nonthermal multicomponent model with the catalytic reactive boundary condition from Arcidiacono et al [13] to account for large temperature differences.…”
Section: Introductionmentioning
confidence: 99%